PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGEMBANGAN BAHAN AJAR BERBASIS WEBSITE - Alif Ringga Persada (EduMa: Mathematics education learning and teaching, 2017)
At globalization era in this time process the study challenge which big relative, related to technological science growth ( Very extraordinary IPTEK). very the fast Growth IPTEK offer to us various amenity in obtaining and mengolah information. Especially vary it study media which can be used by a teacher at the (time) of submitting study items. development of teaching Substance which is is made by by a researcher is substance development teach to base on the Website of at address of web belajarmatematika.id. Intention of this research is : 1)Mengetahui use of study media base on the e-learning ( Website) at school 2) Yielding product of study media " being based on Website of at items develop;build to level off 3) Knowing result learn the student use the Website of at items of parallelogram and segita.4) Getting product of multimedia of mathematics study for the student of class 7 High School Pertama.5) Knowing storey;level of elegibility of multimedia of study of mathematics of class student 7 Junior High School of research Method used in this research is Rnd ( Research And Development)Dengan model the ADDIE with the technique of data collecting use the sheet of enquette and tes. Population in this research is entire/all class of VIII SMP Country 1 Krangkeng of Regency Indramayu of while intake sampel use the technique of Purposive Sampling and chosen of class of VIII E as experiment class. Pursuant to data processing result, obtained by result of analysis of enquette of respon student to substance teach to base on the Website show the strong criterion with the mean of equal to 85,08%. Beradasarkan of result of test of independent sample t test the ( two tailed), knowable that value t_hitung>t_tabel, that is 6,331 > 2,000. Because t_hitung>t_tabel, hence H0 refused and accept Ha, what its meaning there are difference of result of learning at class of experiment and class control at fundamental of discussion segiempat and trilateral Â Keyword: Substance Teach The, Website, Result of Learning